Induction and analysis of gamma ray-induced flower head shape mutation in'Lalima'chrysanthemum (Chrysanthemum morifolium) - BANERJI, B K; DATTA, S K (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the rainy season of 1998 to study the effects of gamma irradiation in 'Lalima' Chrysanthemum (Chrysanthemum morifolium L.) with particular reference to induction of somatic mutation. The rooted cuttings were irradiated with 0, 15,20 and 25 Gy of gamma rays. Reduction in survival, growth, plant height, number of branches and leaves/plant and leaf and flower size and increased morphological, floral and chromosomal abnormalities were recorded after irradiation. Mutation in flower head shape were detected from 25 Gy treatment in M,V, and M,V 2 generation and established in pure form. Comparative cytomorphological and anatomical analysis of original and mutant was carried out to understand the nature of mutation. Significant reduction in plant height, flower head diameter and guard cell width were recorded after irradiation, however no change in chromosome number was recorded in the mutant. Gamma ray-induced flower head shape mutant of 'Lalima' was found very attractive and ideal for pot culture.